Are We Ready? : Public Health Since 9/11. - Rosner, David, 1947- (California/Milbank books on health and the public, 2006)
A contemporary history of a critical period, Are We Ready? analyzes the impact of 9/11, the anthrax attacks that followed, and preparations for a possible smallpox attack on the nation's public health infrastructure. David Rosner and Gerald Markowitz interviewed local, state, and federal officials to determine the immediate reactions of key participants in these events. The authors explore the extent to which these emergencies permanently altered the political, cultural, and organizational life of the country and consider whether the nation is now better prepared to withstand another potential.